2020
DOI: 10.1016/j.nmni.2020.100728
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between vitamin D levels and prevalence of urinary tract infections in children

Abstract: Urinary tract infection (UTI) is associated with increased health burden among paediatric patients. Vitamin D is known for its immunoregulatory effects, particularly antimicrobial activity. The aim of this study was to determine the relationship between vitamin D levels and UTIs in children referred to a hospital in Khorramabad, Iran. This case–control study was conducted on 258 children aged between 2 and 14 years; 44 children with UTI and 214 healthy children were enrolled. Patients were tested for UTI on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 27 publications
2
16
1
Order By: Relevance
“…Vitamin D levels presented a descending trend with thriving in our study, but only in children diagnosed with UTI. This finding is inconsistent with other studies evolving around UTI in children so far, which have not found any significant correlation between age and vitamin D levels [15,34]. The children included in our study benefited from continuous vitamin D prophylaxis until the age of two.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Vitamin D levels presented a descending trend with thriving in our study, but only in children diagnosed with UTI. This finding is inconsistent with other studies evolving around UTI in children so far, which have not found any significant correlation between age and vitamin D levels [15,34]. The children included in our study benefited from continuous vitamin D prophylaxis until the age of two.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrarily to our findings, a study conducted by Tekin et al, which also reported a higher percentage of girls among patients with UTI, claimed that female sex also exhibited lower serum 25(OH)D values [38]. Multivariate analysis also confirmed that female sex represented a risk factor for UTIs, in conjunction with low 25(OH)D levels, similarly to another study evaluating the relationship between vitamin D deficiency and UTIs [34]. Still, sex has also been compared separately on age groups.…”
Section: Discussionsupporting
confidence: 88%
“…The motility of macrophages and their activity are increased by vitamin D. Vitamin D is converted to the active form by macrophages, and the active vitamin D3 regulates the gene expression of antimicrobial peptides that are important for the defense mechanism [ 9 ]. Besides the influence on the immune system, vitamin D can affect bacterial clearance [ 3 ]. Epithelial cell-derived mediators, including antimicrobial peptides, such as α- and β-defensins and cathelicidin, have a profound effect on urinary tract defense.…”
Section: Discussionmentioning
confidence: 99%
“…UTI may have acute and chronic complications in children compared to adults, which usually has a benign course [ 2 ]. It occurs in 1% of boys and up to 5% of girls and is more frequent than bacterial meningitis, otitis media and pneumonia [ 3 ]. A large number of children with symptomatic urinary tract infections are in the first decade of life and are prone to kidney scars and subsequent possible complications such as growth retardation, arterial hypertension, proteinuria and finally, chronic renal failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation